Data Transformation Is the CEO’s Business - Wixom, Barbara; Redzic, Ogi; Hootman, Brandon; Rodriguez, Joaquin; Piccoli, Gabriele; Beath, Cynthia (MIT Sloan Management Review, 2026)
A multiyear data transformation project at Caterpillar that has made the company AI-ready provides an exemplary case for what leadership commitment to such a technology project involves. CEOs must go beyond communicating abstract support, by setting a tangible, strategic business goal that the transformation will support; giving teams realistic time horizons and adequate resources; and assigning meaningful, instrumental roles to members of the leadership team.